Fleece-Bound Tissue Sealing in Microvascular Decompression - Tanrikulu, Levent; Buchfelder, Michael; Naraghi, Ramin (Turkish Neurosurgery, 2017)
AIM: Cerebrospinal fluid (CSF) leakage is a feared complication after microvascular decompression (MVD). In this study, we present our experience of fleece-bound tissue sealing in MVD with an aim to minimize the rate of postoperative CSF leakage. MATERIAL AND METHODS: We treated 50 patients (female/male: 26/24) with neurovascular compression (NVC) syndromes (trigeminal neuralgia, hemifacial spasm and glossopharyngeal neuralgia) by MVD from 2003 to 2006. All patients underwent retromastoid craniectomy and duraplasty by fleece-bound tissue sealing using the so-called "sandwich technique" by a three-layer reconstruction and cranioplasty. RESULTS: In 49 (98%) of 50 patients, we did not observe postoperative CSF leakage. One patient (2%) suffered postoperative CSF leakage and required surgical revision. CONCLUSION: Fleece-bound tissue sealing by a three-layer reconstruction is effective and safe in the prevention of cerebrospinal fluid leakage in microvascular decompression.
EVALuna2:102198